Hierarchical Fe3O4@TiO2 Yolk–Shell Microspheres with Enhanced Microwave‐Absorption Properties. Issue 21 (20th March 2013) - Liu, Jiwei; Xu, Junjie; Che, Renchao; Chen, Huajun; Liu, Mengmei; Liu, Zhengwang
Abstract A facile and efficient strategy for the synthesis of hierarchical yolk–shell microspheres with magnetic Fe3O4 cores and dielectric TiO2 shells has been developed. Various Fe3O4@TiO2 yolk–shell microspheres with different core sizes, interstitial void volumes, and shell thicknesses have been successfully synthesized by controlling the synthetic parameters. Moreover, the microwave absorption properties of these yolk–shell microspheres, such as the complex permittivity and permeability, were investigated. The electromagnetic data demonstrate that the as‐synthesized Fe3O4@TiO2 yolk–shell microspheres exhibit significantly enhanced microwave absorption properties compared with pure Fe3O4 and our previously reported Fe3O4@TiO2 core–shell microspheres, which may result from the unique yolk–shell structure with a large surface area and high porosity, as well as synergistic effects between the functional Fe3O4 cores and TiO2 shells.